1996
DOI: 10.2307/1131778
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Use of Inductive Discipline: Relations to Children's Empathy and Prosocial Behavior

Abstract: Relations between parents' discipline, children's empathic responses, and children's prosocial behavior were examined in order to evaluate Martin Hoffman's claim that children's empathy and empathy-based guilt mediate the socialization of children's prosocial behavior. 78 sixth and seventh graders (138-172 months in age), their mothers, and teachers completed multiple measures of Hoffman's constructs. Results were largely consistent with theory. Parents' use of inductive as opposed to power-assertive disciplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(86 citation statements)
references
References 0 publications
6
70
2
8
Order By: Relevance
“…There is an abundance of phenotypic research that shows that parenting practices are associated with compliance, empathy, and prosocial behaviors (e.g., Braungart-Rieker, Murphy Garwood, & Stifter, 1997;Deater-Deckard et al, 2001;Eisenberg & Fabes, 1998;Krevans & Gibbs, 1996;Whiteside-Mansell et al, 2003). Our findings of prodigious shared environmental influences on behavioral competencies would be consistent with parenting research in early childhood and suggest that there are family-wide effects that influence the development of behavioral competencies and thus make young siblings similar within this behavioral domain.…”
Section: Behavioral Competenciessupporting
confidence: 82%
See 1 more Smart Citation
“…There is an abundance of phenotypic research that shows that parenting practices are associated with compliance, empathy, and prosocial behaviors (e.g., Braungart-Rieker, Murphy Garwood, & Stifter, 1997;Deater-Deckard et al, 2001;Eisenberg & Fabes, 1998;Krevans & Gibbs, 1996;Whiteside-Mansell et al, 2003). Our findings of prodigious shared environmental influences on behavioral competencies would be consistent with parenting research in early childhood and suggest that there are family-wide effects that influence the development of behavioral competencies and thus make young siblings similar within this behavioral domain.…”
Section: Behavioral Competenciessupporting
confidence: 82%
“…On the basis of prior behavioral genetic research with empathy and prosocial behavior, we predicted that behavioral competencies on the ITSEA would be influenced by genetic factors. Moreover, because prosocial behaviors in toddlers have been linked to parenting practices (e.g., Deater-Deckard, Dunn, O'Connor, Davies, & Golding, 2001;Eisenberg & Fabes, 1998;Knafo & Plomin, 2006a;Krevans & Gibbs, 1996; Whiteside-Mansell, Bradley, Tresch Owen, Randolph, & Cauce, 1998), it was also predicted that early behavioral competencies would show substantial shared environmental variance. …”
mentioning
confidence: 99%
“…A positive relation between maternal warmth/ support or sensitivity and children's and adolescents' altruistic and pro-social responding was obtained ( Krevans, Gibbs, 1996). Research in the field of parenting style has often focused on the effect of the mother's style, or has considered the average score from both parents.…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrating that empathy can partly predict EATEH agrees with previous research on empathy. Firstly, a large body of research has demonstrated that empathy is related to moral, caring, and prosocial behavior because it involves giving help to someone who is in trouble or distress (Barnett, Howard, King, & Dino, 1981;Batson et al, 1999;Batson et al, 1995;Hoffman, 1977Hoffman, , 2001Krevans & Gibbs, 1996;Shelton & Rogers, 1981) and who might belong to a different group (Batson et al, 1991). Secondly, it has been found that empathy can influence individual's attitude toward members of another group (Batson et al, 1997) whereas lack of empathy relates to intergroup aggression (Struch & Schwartz, 1989;Wang et al, 2003), social dominance orientation (Pratto, Sidanius, Stallworth, & Malle, 1994), and prejudice (Bäckström & Björklund, 2007;Johnson, Brems, & Alford-Keating, 1997;Whitley Jr, 1999).…”
Section: Discussionmentioning
confidence: 99%